Strategies for Revitalizing Universitas Mulawarman Botanical Garden (KRUS) as a Flora and Fauna Educational Tourism Destination Utilizing SWOT Analysis - Ilmi, Annisa Nurul; Rahmawati, Dewi; Waskito, Wasis (Universitas Terbuka, 2025)
Samarinda's Universitas Mulawarman Botanical Garden or Kebun Raya Universitas Mulawarman Samarinda (KRUS) has an important role in biodiversity conservation, environmental education, and flora and fauna-based ecotourism. However, in recent years, KRUS has faced challenges in management and tourist attraction so that it has decreased its function. This study aims to analyze the revitalization strategy of KRUS as a conservation-based edu-tourism using SWOT analysis. The method used is a literature study with a qualitative approach based on content analysis of various scientific sources related to botanical garden management strategies. The results showed that KRUS has advantages in the form of diversity of Kalimantan endemic flora and fauna and its potential as an environmental education center. However, the main challenges faced are limited infrastructure, environmental degradation, and lack of promotion and community involvement. To overcome these problems, the proposed strategies include Strengthening development of educational tourism packages, diversifying education-based tourism attractions, and increasing collaboration with academic institutions and communities, and utilization of digital technology for promotion and education. The implications of this research emphasize the importance of synergy between academics, government, and the community in sustainable botanical garden management. Further research is needed to evaluate the effectiveness of the strategies implemented and their impact on environmental conservation and the local economy.